Managing chronic disease in the COVID-19 pandemic: an e-learning application to promote a healthy lifestyle for persons with multiple sclerosis. Issue 2 (7th February 2022) - d'Arma, A.; Rossi, V.; Pugnetti, L; Grosso, C.; Sinatra, M.; Dos Santos, R.; Di Giusto, G.; Mendozzi, L.
ABSTRACT: E-health applications can support continuing care for persons with chronic diseases such as multiple sclerosis (MS). We have developed a web-based mobile app called VIOLA to be used at home by persons with MS (pwMS) who previously participated in an innovative multidisciplinary rehab program. The purpose of VIOLA is to reinforce what participants have learned about a healthy lifestyle and to keep them motivated to adhere to rehabilitation programs. As the outbreak of the Covid-19 pandemic has severely curtailed pwMS contact with their usual health providers, we quickly updated VIOLA to grant continuity of care to our home-bound patients. By monitoring pwMS subscriptions to individual modules, we found a definite increase after the national lockdown was declared. Subscribers rated the app very positively. Encouraged by the positive feedbacks, we are planning to extend the access to our app also to pwMS with no prior specific learning experience. This would limit the psychophysical consequences of the lockdown. Furthermore, VIOLA could be effective in maintaining a proper lifestyle, contributing to improve the quality of life of pwMS. VIOLA has the potential of increasing the adherence of pwMS to the rehabilitation confirming that digital communication tools are a valuable solution for those home-bound.]